.Pilot study of quality control of Artemisia annua-based herbal medicine sold in Benin. - ASSANHOU, Assogba Gabin (My University, 2019)
The quality control of medicines is one of the key factors which determine its efficacy. In Africa, particularly in Benin, a large population often uses traditional medicines. Therefore, controlling their quality becomes a major concern for public health. It is in this context that this study was designated to ensure an adequate system of drugs quality control, especially herbal medicines. We collected three different samples (T1, T2 and T3) of Traditional Medicines (MTA) based on Artemisia annua and we controlled their quality. The identification of artemisinin was carried out by Thin Layer Chromatography (TLC) and the quantification by High Performance Liquid Chromatography (HPLC). After analyzing the organoleptic characteristic, the loss of water and the impurities, we found that only T3 was conform to all the specification as MTA. This work opens a new platform of expertise in the field for our team and further a hope for the management of public health in term of the control of MTA.